NUMBER OF 2p-PERIODIC SOLUTIONS OF THE NONAUTONOMOUS EQUATION IN THE WHOLE PLANE - Yasmin, Nusrat; Sultana, N. (Journal of Research (Science), 2001)
2p-periodic solutions of certain one dimensional non-autonomous cubic differential equations are investigated in the whole plane when the coefficient of cubic term in the equation does not change sign, using the transformations (1.3). Also we have proved that the transformation can be applied to non-homogeneous system (4.1) for possible investigation of 2p-periodic solutions.